Neophotistoi and Apostates: Greece and Conversion in the Nineteenth Century - Doxiadis, Evdoxios (Historein, 2022)
Greek historiography no longer ignores the massacres of non-Christians during the Greek War of Independence, but little thought is given to the fate of those Muslims and Jews that survived or how their presence, as non-Christians or as new converts, impacted the new state, its ideology, structures, policies or laws. This article begins to address this gap and attempts to highlight the seriousness with which Greek governments, both in the revolutionary and post-independence periods, confronted this issue. Using a variety of sources such as wills and dowry contracts, court cases, government records and revolutionary memoirs, the article attempts to show that modern historiography has underestimated the numbers and significance of converts and conversion, and that in this regard Greece and the Ottoman Empire share remarkable similarities in their treatment of conversion, the conflicts it generated, and the use of religion to shore up political weakness. As in the Ottoman Empire, conversion was a thorny issue for the early Greek governments that were trying to establish their legitimacy in the international arena. At the same time it provided opportunities for Greece to assert its influence far beyond its physical capacities, presenting itself as the defender of Orthodox Christians, a role previously monopolised by the Russian Empire.